Episode from Jinadatta Suri's life - Temples of India Project (Jio Institute, 2024)
The thirteenth oval painting (in clockwise order) in the lower/outer circle in the ceiling of the mandapa (pillared hall) is the episode from Jinadatta Suri's life that took place in Ajmer. Once, an ominous stroke of lightning in the evening threatened the fellow monks and followers of Dada Jin Dutt Suri while they were performing pratikraman with him. Dada Jin Dutt Suri captured the lightning under his alms bowl and instructed everyone to continue with the pratikraman without fear. Lightning is shown as yellow strokes in the sky that the acharya (those who impart knowledge) collected in the bowl. Jinadatta Suri is shown sitting on a mat. The inscription reads, ‘shri jinadatta suri ji Bijali dabi.’